Long term sedimentation of an elliptic disc subject to an electrostatic field using smoothed particle hydrodynamics method - Tofighi, N.; Feng, J.J.; Yildiz, M.; Suleman, A. (International journal of multiphase flow, 2021)
highlights•Long term sedimentation of an ellipse subject to an external electric field is studied.•Horizontal, slanted, vertical and oscillating sedimentation behaviors are observed solely due to electrical forces.•Electrical forces lead to slower descent in narrow channels while the reverse happens in wider channels.•We observe no significant change in long term behavior due to different initial orientations.•The electrical effects are more pronounced at higher density ratios. A two dimensional incompressible smoothed particle hydrodynamics scheme for long term sedimentation of rising or falling particulates (bubbles, drops or rigid particles) in Newtonian fluids is presented and validated by simulating the sedimentation of a single elliptic disc. The proposed method is then used to simulate the sedimentation of an elliptic disc subject to an external electric field parallel to the gravitational field. A range of electric field intensities, permittivity ratios, blockage ratios and density ratios are covered in this study. The results show that for given blockage and density ratios, the final sedimentation orientation of the ellipse is dependent on a combination of permittivity ratio and electric field intensity, ranging from horizontal to vertical. Compared to non-electrified sedimentation, an increase in electric field intensity and permittivity ratio lead to vertical sedimentation. As the channels grow wider, the presence of electric field leads to faster ellipse descent, regardless of its initial orientation.